(untitled) (Journal on Excellence in College Teaching, 2024)
The University of North Carolina at Pembroke, a historically American Indian university that is experiencing major climate change impacts from hurricanes, was the setting for four service-learning projects seeking to advance sustainability in a racially diverse community. Courses in American Indian Studies, English, and Social Work, in collaboration with farms, schools, and community organizations, demonstrated benefits to student learning and retention and sought to fulfill faculty members’ aspirations for enhanced community wellbeing. In addition to first-person narratives of these activities, the authors provide resources for adaptation and/or usage in higher educational settings.